UNSUR KOHESI PADA NASKAH DRAMA SENJA DENGAN DUA KELELAWAR DAN PEMANFAATANNYA DALAM PEMBELAJARAN SASTRA DI SEKOLAH MENENGAH ATAS - Lathifudin, Abdullah; Suwandi, Sarwiji; Rohmadi, Muhammad (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to describe: (1) cohesive devices in drama script Senja dengan Dua Kelelawar by Kirdjomuljo, and (2) the relevance of cohesive devices on drama script Senja dengan Dua Kelelawar with Indonesian language learning in high school. This research is linguistic qualitative research with content analysis method. The data sources used are documents and informants. The sampling technique uses purposive sampling technique. Data collection techniques use scrutinize method and interview method. Data validity is done by theory triangulation and data source triangulation. Data analysis using interactive analysis techniques. The results of the study show: (1) cohesive devices found in drama script Senja dengan Dua Kelelawar covering grammatical cohesion with sub-types (a) pronouns, (b) recovery, and (c) lapse, lexical cohesion with subtitles (a) repetition, (b ) synonym, (c) hyponym, (d) meronym, and (e) collocation, and conjunction with sub-types (a) coordinative conjunctions, and (b) subordinate conjunctions. The most dominant elements are pronouns and conjunctions; (2) cohesion devices in drama scripts Senja dengan Dua Kelelawar have relevance to Indonesian language learning, especially material about the linguistic elements of text in 10th grade, 11th grade, and 12th grade high school.